DOI: 10.1007/978-3-540-69132-7_65
|View full text |Cite
|
Sign up to set email alerts
|

To Tutor the Tutor: Adaptive Domain Support for Peer Tutoring

Abstract: Abstract. The effectiveness of intelligent tutoring systems at increasing learning might be improved if the systems were combined with collaborative activities that encouraged conceptual elaboration. We extended the Cognitive Tutor Algebra, an intelligent tutoring system for high-school mathematics, with a peer tutoring activity that was designed to encourage interaction, reflection, and accountability. Two types of domain support were provided: adaptive support, which used the intelligent tutor domain models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…How can the need for support be diagnosed in real time? Such questions are in the center of interest in current research endeavors in CSCL (e.g., Gweon et al 2006;Soller et al 2005;Walker et al 2008). However, while interest in adaptive support for collaborative learning is on the rise, little progress has yet been made on its implementation.…”
Section: Discussionmentioning
confidence: 95%
“…How can the need for support be diagnosed in real time? Such questions are in the center of interest in current research endeavors in CSCL (e.g., Gweon et al 2006;Soller et al 2005;Walker et al 2008). However, while interest in adaptive support for collaborative learning is on the rise, little progress has yet been made on its implementation.…”
Section: Discussionmentioning
confidence: 95%
“…The current study investigated the tutor learning effect in algebra equation solving that has more procedural skills involved in nature. Notably, Walker et al [11] found no significant benefit of peer tutoring (within students alternating between tutoring and being tutoring) over being tutored in a procedural domain. The presence of the ATI suggests that there might be more requirements for prior knowledge when teaching procedural skills than when teaching declarative knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Certified learners can be invited to be mentors, helping instructors out with answering questions, giving tips, even sharing own struggles while studying the course. Research have shown that the act of tutoring others will boost learners' conceptual elaboration, enhancing the transferability of acquired knowledge [22].…”
Section: A Create a Stronger Sense Of Communitymentioning
confidence: 99%